2017
DOI: 10.1111/1751-2980.12486
|View full text |Cite
|
Sign up to set email alerts
|

Serine protease inhibitor Kazal type 1 (SPINK1) downregulates E‐cadherin and induces EMT of hepatoma cells to promote hepatocellular carcinoma metastasis via the MEK/ERK signaling pathway

Abstract: SPINK1 may be an oncogene that induces EMT via the MEK/ERK pathway and is a potential target for HCC therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Experiments involving pharmacological blocking of MEK revealed that suppression of ERK is involved in RAC1B-mediated inhibition of cell migration, prevention of TGF-β1-induced downregulation of CDH1 and TGF-β1-mediated upregulation of SNAI1 (see Figure 5). While MEK-ERK signaling has been implicated before in downregulation of CDH1 by epidermal growth factor, serine protease inhibitor Kazal type 1, and activin B [38][39][40], our observation that TGF-β employs the same pathway to silence CDH1 is novel. The partial reversal of migratory activity in RAC1B knockdown cells and the TGF-β1-dependent decrease in E-cadherin expression by U0126 may be secondary to U0126-mediated inhibition of TGF-β1-induced upregulation of SNAIL since SNAIL is a potent inhibitor of CDH1.…”
Section: Discussionmentioning
confidence: 60%
“…Experiments involving pharmacological blocking of MEK revealed that suppression of ERK is involved in RAC1B-mediated inhibition of cell migration, prevention of TGF-β1-induced downregulation of CDH1 and TGF-β1-mediated upregulation of SNAI1 (see Figure 5). While MEK-ERK signaling has been implicated before in downregulation of CDH1 by epidermal growth factor, serine protease inhibitor Kazal type 1, and activin B [38][39][40], our observation that TGF-β employs the same pathway to silence CDH1 is novel. The partial reversal of migratory activity in RAC1B knockdown cells and the TGF-β1-dependent decrease in E-cadherin expression by U0126 may be secondary to U0126-mediated inhibition of TGF-β1-induced upregulation of SNAIL since SNAIL is a potent inhibitor of CDH1.…”
Section: Discussionmentioning
confidence: 60%
“…Low expression of miR‐448 induces EMT and promotes invasion by regulating ROCK2 in HCC . Serine protease inhibitor Kazal type 1 downregulates E‐cadherin and induces EMT of hepatoma cells to promote HCC metastasis via the MEK/ERK signaling pathway . Small nucleolar RNA 47 promotes tumorigenesis by regulating EMT markers in HCC .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SPINK1 secreted by cancer cells could coimmmunoprecipitate with serine protease granzyme A (GzmA), a cytolytic granule secreted by natural killer cells and cytotoxic T lymphocytes, thereby suppressing GzmA-mediated apoptosis and establishing a tolerance of cancer cells to the immune surveillance system (32). More importantly, SPINK1, as a growth factor, is aberrantly expressed in multiple human cancers such as ovarian cancer (33), prostatic cancer (36), colorectal cancer (37), hepatocellular carcinoma (38) and pulmonary adenocarcinoma (39). Based on big data analysis, we detected a significant increase of SPINK1 expression in NSCLC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It has been universally accepted that SPINK1 acting as a pro-survival factor accelerated the progression of multiple cancers by interacting with EGFR ( 25,28,29,38,53). In order to clarify signaling pathways downstream of EGFR mediating the carcinogenic effect of SPINK1 in NSCLC, the phosphorylation levels of MEK1/2, ERK, PI3K and AKT were assessed by western blot.…”
Section: Spink1 Accelerates the Proliferation Of Nsclc Via Activationmentioning
confidence: 99%